Assessment of Economic Growth in Romania. Is it a Sustainable One? - Iacobuta, Andreea-Oana; Asandului, Laura; Cautisanu, Cristina (European Journal of Sustainable Development, 2020)
Sustainable economic growth assumes interdependencies among social, economic, and environmental dimensions of growth. For Romania, in particular, the sustainable economic growth is both a challenge and an opportunity for prosperity. This paper aims at assessing the sustainability of economic growth in Romania in the period 1995-2019 by identifying the social, economic, environmental, and institutional drivers of the process of economic growth. Multivariate time-series analysis was used to analyse if the Romanian economic growth in the period 1995-2019 is sustainable. We also estimated the GDP per capita growth rate based on the determinants with which we found significant relationships. Keywords: sustainable economic growth; Romania, GDP per capita growth rate; socio-economic, environmental, and institutional factors; multivariate time-series analysis; multiple regression model